Avatar Intervention in Virtual Reality for Cannabis Use Disorder in Individuals With Severe Mental Disorders: Results From a 1-Year, Single-Arm Clinical Trial - Sabrina Giguere; Mélissa Beaudoin; Laura Dellazizzo; Kingsada Phraxayavong; Stéphane Potvin; Alexandre Dumais (JMIR Mental Health)
Abstract BackgroundThe dual diagnosis of cannabis use disorder (CUD) and severe mental disorder (SMD) results in clinically complex individuals. Cannabis use is known to have negative consequences on psychiatric symptoms, medication compliance, and disease prognosis. Moreover, the effectiveness of currently available psychotherapeutic treatments is limited in this population. In this context, our research team developed avatar intervention, an approach using virtual reality as a therapeutic tool to treat CUD in individuals with SMD. ObjectiveThis pilot clinical trial aimed to evaluate, until the 1-year follow-up, the efficacy of avatar intervention for CUD among 32 participants with a dual diagnosis of SMD and CUD. MethodsOver the course of the 8 intervention sessions, participants were given the opportunity to enter a dialogue in virtual reality with an avatar representing a person with a significant role in their consumption, who was animated in real time by a therapist. The primary outcomes were the quantity of cannabis consumed and the frequency of use. Secondary outcomes included severity of problematic cannabis use, motivation for change, protective strategies for cannabis use, consequences of cannabis use, psychiatric symptoms, and quality of life. Changes in reported outcomes during the assessment periods before the intervention; postintervention; and 3, 6, and 12 months after the end of the intervention were assessed using a linear mixed-effects model. ResultsSignificant reductions were observed in the quantity of cannabis consumed, and these were maintained until the 12-month follow-up visit (dPdP ConclusionsOverall, this unique intervention shows promising results that seem to be maintained up to 12 months after the end of the intervention. With the aim of overcoming the methodological limitations of a pilot study, a single-blind randomized controlled trial is currently underway to compare the avatar intervention for CUD with a conventional addiction intervention.